In-plane cyclic response of unreinforced masonry walls retrofitted with ferrocement. (December 2022) - Hasnat, Abul; Das, Tanmoy; Ahsan, Raquib; Alam, Ahmed Tohameem; Ahmed, Hafiz
Abstract: Unreinforced masonries are weak against seismic loads which necessitates their retrofitting. Ferrocement is widely used as it is cheaper than alternative methods of retrofitting. Some crucial parameters can significantly affect the performance of such retrofitted structures under cyclic loading conditions, such as: aspect ratio, difference of wire mesh arrangements & pattern of retrofitting. To quantify the impact of these parameters, this study has implemented two variations of each parameter. This study conducts experimental investigations of the ferrocement retrofitted unreinforced masonry walls (URM) and evaluation of their properties such as energy dissipation, stiffness degradation, hysteretic damping, ductility, and load deformation responses. Results show notable increase in strength after ferrocement retrofitting of URM walls. Retrofitting of URM walls with inexpensive material such as ferrocement is gaining popularity, our research is guided towards finding the in-plane cyclic load characteristics of such method of retrofitting. Sample walls were prepared in two categories: (1) Long walls (aspect ratio 0.57) and (2) Short walls (aspect ratio 1). A total of ten clay masonry walls (five for each category) were constructed with reinforced concrete base slab. The first variable parameter for the tests was ferrocement coating difference. Some sample walls were retrofitted completely even the base slab & wall panel connection point while on some walls the ferrocement lamination was only applied on the wall panels. Steel wire mesh's opening size is another crucial variable test parameter. Two different wire mesh opening sizes: (1) 3.2 × 3.6 mm and (2) 8.5 × 8.5 mm were used on the walls. One control specimen with no retrofitting for both short and long walls were prepared for test comparison purpose. Laterally reversed cyclic loads and vertical loads both were applied to the sample walls during tests. Improvements in hysteretic damping, stiffness, energy dissipation and ductility were scrutinized in particular. Finally, a comparison was drawn between the test findings and allowable load provisions prescribed in the Bangladesh National Building Code (BNBC) 1993.